WORKSHOP RADIOLOGI TATA LAKSANA PEMERIKSAAN HSG PADA KASUS INFERTILITAS SERTA SOSIALISASI PENGISIAN SIPORLIN DAN MANAJEMEN ORGANISASI - Aulia Annisa; Danil Hulmansyah; Shelly Angella; R. Sri Ayu Indrapuri (Awal Bros Journal of Community Development, 2023)
The PARI Pengda Riau organization as one of the health professions in Riau Province, never stops trying to improve the professional skills of Radiographers through Workshop or Seminar activities, both local, regional, national and international. This activity is very important so that Radiographers in Riau Province can find out various information about technological developments in the field of Radiology and applicable laws so that they can work with high professionalism and responsibility. For this reason, we intend to hold community service in the form of a local workshop in collaboration with radiology professional organizations with the title "Procedure for HSG Examinations in Infertility Cases and Socialization of Filling in Siporlin and Organizational Management". Hopefully this workshop will have a positive impact on radiographers and make a meaningful contribution to the world of health. The method used in this service activity is presentation of material from several resource persons and event sponsors as well as a demonstration of how to update STR on the SIPORLIN application and questions and answers. The target of this training is Radiographers and Students. The result of this training is that the workshop activities ran well and smoothly and were able to improve their abilities in updating knowledge in the field of radiology, especially and regulations related to updating information related to the Health Law.